2012
DOI: 10.1007/s11262-012-0776-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and molecular characterization of enteroviruses from sewage-polluted urban and rural rivers in the Philippines

Abstract: Despite the vast distribution and expansive diversity of enteroviruses reported globally, indicators defining a complete view of the epidemiology of enteroviruses in tropical countries such as the Philippines are yet to be established. Detection of enteroviruses in the environment has been one of the markers of circulating viruses in a community. This study aimed to bridge the gap in the epidemiology of enteroviruses in the Philippines by providing an overview of the occurrence of enteroviruses in both urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
4
21
1
Order By: Relevance
“…The isolation of these pathogens among healthy population is considered an important factor in the continuous circulation of the disease in the community [6,9]. These EV types were also detected in previous studies on NPEVs among AFP cases and environmental samples in the Philippines, which may be suggestive of indigenous circulation of these pathogens in the country [7,20]. Further analysis indicated that the EV-A71 in this study belonged to genogroup C, specifically the C2 cluster which is genetically homologous to the EV-A71 C2 cluster reported among AFP cases [15].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The isolation of these pathogens among healthy population is considered an important factor in the continuous circulation of the disease in the community [6,9]. These EV types were also detected in previous studies on NPEVs among AFP cases and environmental samples in the Philippines, which may be suggestive of indigenous circulation of these pathogens in the country [7,20]. Further analysis indicated that the EV-A71 in this study belonged to genogroup C, specifically the C2 cluster which is genetically homologous to the EV-A71 C2 cluster reported among AFP cases [15].…”
Section: Discussionsupporting
confidence: 53%
“…All of the detected EV serotypes among healthy children mirror the EV serotypes isolated from AFP cases and environmental samples in previous reports except for the detection of CV-A22. The detection of CV-A22 in the Philippines was first identified and documented in this study [7,20].…”
Section: Discussionmentioning
confidence: 65%
“…However, species C EV serotypes were abundant in sewage in the Edinburgh, including CAV1, CAV13, CAV19, CAV22 and a possible new EV type. Species C enteroviruses were also the most commonly detected viruses in sewage screening on the Philippines [21]. This dichotomy is best explained by a specifically lower pathogenicity of non-polio EV-C variants [3].…”
Section: Diversity Of Enterovirusesmentioning
confidence: 99%
“…Environmental surveillance is a highly sensitive method for detecting enteroviruses such as PVs in environmental samples, and this practice has been adopted by many countries and regions worldwide (13)(14)(15)(16)(17)(18)(19). It is critically important to routinely monitor sentinel sites for the emergence of novel VDPV strains and the importation of wild PV from countries where the disease is endemic.…”
mentioning
confidence: 99%